Conversation Circles as a Teaching Strategy: An Experience to Reflect on and Implement in Higher Education - Arias Monge, Mónica (Revista Electrónica Educare, 2012)
The experience approached in this paper aims at reflecting, reasoning, planning and implementing the “Conversation Circles” as a teaching strategy in the PF-4237 course “Theory of Education: Multiculturalism and Education” of the Latin American Doctoral Program in Education, University of Costa Rica. This training experience, based on the communicative action theory, intended to integrate the assistance of the teacher, the confrontation to otherness and the building of knowledge, skills and social attitudes in higher education.